Evaluation of Comprehensive Management Protocol for Reduction of the Risk of Fragility Fractures Among Osteoporosis Individuals, Visiting Teaching Hospital, Kolkata - Pal, Chhanda; Adhikari, Uma; Pal, Ananda Kisor (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: Fragility fracture from osteoporosis is a major challenging health problem in aging population in developing countries. In order to reduce the risk of development of osteoporotic fragility fractures authors made a study with high risk individuals, divided into two groups and a comprehensive management protocol had been offered in one group where as conventional management protocol had been offered in other to see the efficacy of such comprehensive management protocol to reduce the risk of occurring fragility fracture over at least three months period among the patients, attended in orthopaedic out patient department of state medical college, West Bengal. Methods: The authors selected 30 diagnosed osteoporosis clients of 50 to 90 years age as per inclusion and exclusion criteria, who attended in orthopaedic OPD in SSKM Hospital, Kolkata, West Bengal, India from 2021April to July2021, carrying highest risk factors of developing osteoporosis. Results: In experimental group, mean post test BMD score is higher than the mean pre test BMD, which is statistically significant as calculated t value is 3.666 at 14 df at 0.05 (p<0.05) level of significances. It indicates that comprehensive management protocol is effective to increase the bone strength. Conclusion: The study of comparison of mean difference values of two groups conclude that comprehensive management protocol can reduce the risk of osteoporotic fracture much efficiently in compared to standard pharmaceutical treatment in a short span of time which is applicable for long term management of osteoporosis.